Phenothiazine-based covalent organic frameworks with low exciton binding energies for photocatalysis - Wang, Weitao; Wang, Haotian; Tang, Xiaohui; Huo, Jinlei; Su, Yan; Lu, Chuangye; Zhang, Yujian; Xu, Hong; Gu, Cheng (Chemical science (Cambridge), 2022)
Designing delocalized excitons with low binding energy ( E b ) in organic semiconductors is urgently required for efficient photochemistry because the excitons in most organic materials are localized with a high E b of >300 meV. In this work, we report the achievement of a low E b of ∼50 meV by constructing phenothiazine-based covalent organic frameworks (COFs) with inherent crystallinity, porosity, chemical robustness, and feasibility of bandgap engineering. The low E b facilitates effective exciton dissociation and thus promotes photocatalysis by using these COFs. As a demonstration, we subject these COFs to photocatalytic polymerization to synthesize polymers with remarkably high molecular weight without any requirement of the metal catalyst. Our results can facilitate the rational design of porous materials with low E b for efficient photocatalysis. We report the construction of phenothiazine-based covalent organic frameworks, which exhibited diverse structures, the feasibility of bandgap engineering, and unprecedented ultralow exciton binding energy of ∼50 meV for photocatalytic polymerization.